The Sensitivity of Aerodynamic Forces to Multi-parameters in a Bird-like Flapping Wing - Changtao Ding; Yuanjun Lv; Min Lu (Journal of Engineering and Technological Sciences, 2018)
The sensitivity of aerodynamic forces in a bird-like flapping wing was numerically studied by analyzing the aerodynamic force states under different parameters. First, the physical model and the kinematic model of the bird-like flapping wing were separately established. Then the aerodynamic force model was established and some important parameters were analyzed by adopting the Taguchi orthogonal method. Finally, a simulation was carried out, from which the order of the parameters was separately determined according to the parameters' effect on lift or thrust. The results showed that increasing the flapping frequency is one of the most important ways to increase lift and thrust. The lift can be increased by increasing the flight velocity, while the thrust can be increased by increasing the maximum flapping angle. The lift or the thrust becomes larger when the incidence angle is approximately or .